Sosialisasi Pengelolaan Sampah Dan Pembuatan Obat Jentik (Sereh) - Anisa Ananda; Ojo Muhamad Sariffudin; Marisa Endah Sari; Rizki Muhammad Somun; Celsy Apriavanka; Dinda Mareta Fisabillah; Dini Wulandari; Qori Ladan Kinasih; Muhammad Rudin; Tri Nabila; Izhad Fiddun Ilyas Sani; Moch Ferriawan (CV. SINAR HOWUHOWU, 2026)
Environmental health problems, particularly Dengue Hemorrhagic Fever (DHF), remain a serious threat to communities in densely populated residential areas. This disease is caused by the dengue virus, which is transmitted through Aedes aegypti mosquitoes that breed in standing water, especially those resulting from improper household waste management. The Thematic Community Service Program (KKN Tematik) of Pekalongan University for the 2025/2026 Academic Year carries the theme “Creating a Healthy and Prosperous Society through Sustainable Waste Management Empowerment Programs.” One of the implemented programs was a socialization activity on the production of natural mosquito larvicide made from lemongrass. This activity aimed to increase community knowledge and awareness of dengue prevention through the use of environmentally friendly natural materials while encouraging sustainable waste management practices. The implementation methods included observation, socialization, training, and mentoring. The results of the activity showed an increase in community understanding of the dangers of mosquito larvae as well as the community’s ability to independently produce and use lemongrass-based larvicides.